Transformer Monitoring and Protection in Dynamic Power Systems – A Review - Xie, Boqi; Zhao, Dongbo; Hong, Tianqi (Frontiers in Energy Research, 2020)
Increasing distributed energy resources, especially the renewable energy resources (RESs) are being installed across power systems these years. These RESs, including solar photovoltaic, wind turbines, etc., provide opportunities for operators to improve power quality, enhance power system resilience, and help meet green energy goals. However, RESs also bring challenges to the operators. As the operating conditions of RESs vary drastically, power systems may experience larger dynamics compared with the traditional power systems with limited RESs. Such dynamics may impose some impacts on devices in power systems. Transformer, as one of the critical and expensive components in power systems, is in need to be protected and monitored constantly. With this said, monitoring and protection of transformers are significant and critical in power system industry as well as in academic research. This paper presents a comprehensive review of the existing transformer monitoring and protection methods. The paper first introduces monitoring and protection approaches for the legacy low frequency transformers, as those transformers are still playing a major role between low frequency interfaces. Then, the literature of the protection of solid-state transformers (SSTs), i.e., power electronics-based transformers, is investigated. A summary of the present technology of transformer monitoring and protection follows.